Respuesta :
Answer:
[tex] \frac{1}{m - n} - \frac{m + n}{m {}^{2} - n {}^{2} } [/tex]
Factor if necessary:
x²-y²=(x+y)(x-y) use this formula
[tex]\frac{1}{m - n} - \frac{m + n}{ {(m + n)(m - n)}}[/tex]
[tex]\frac{1}{m - n} - \frac{1}{ {(m - n)}}[/tex]
Take lcm and subtract:
=0
Answer:
0
Step-by-step explanation:
We need to simplify the given expression . The given expression is ,
→ 1/ ( m - n) - (m + n)/ ( m² - n² )
→ 1/ ( m - n) - ( m + n)/(m+n)(m-n)
- Using a² - b² = (a+b)(a-b)
- Now cancel m+n in numerator and denominator .
→ 1/( m - n) - 1/ ( m - n)
→ 0